Assessing the relationship between adverse childhood experiences (ace) and high HIV risk behaviours among male and female adolescents: A cross sectional study in Balaka, Malawi - Kaponda, Alice Siyenunu (Kamuzu University of Health Sciences, 2022)
Human Immunodeficiency Virus (HIV) remains a burden in Malawi with high incidences among adolescents (0.23% per year). Adverse childhood experiences (ACEs) are a range of events (that children can experience early in their life that leads to stress and can result in trauma and unhealthy behaviours eg sexual immorality, indulging in substance abuse. There are a number of behaviours that exposes one to high HIV risks eg multiple sexual partners and infrequent condom use. The study assessed the relationship between reported adverse childhood experiences and sexual risk behaviours among adolescents’ in Balaka district. This was a cross-sectional study design. It used secondary data from the Malawi Longitudinal Study of Families and Health (MLSFH) study. This study used data from the 2017/2018 data collection wave which interviewed adolescents aged between 10-19. Logistic regression analysis was performed in STATA v14 to assess the association between ACEs and HIV risk behaviours (multiple sexual partners and infrequent condom use). Adolescents who reported having exposed to physical abuse were 1.5771 times likely to have multiple sexual partners as compared to those who were not exposed to reported physical abuse (OR=1.5771, Cl = 0.7879 – 3.1566 at 95%) and AOR was 1.4245 among the exposed. Adolescents exposed to physical abuse and sexual abuse had 1.3019 and 1.4048 respectively risk of not Infrequently use condoms amongst the exposed than in the non-exposed. No association was found between reported emotional abuse and infrequent condom use (OR=1). The study revealed that there was an association between ACEs and sexual risk behaviours. There is a need to institutionalise comprehensive sexuality education from lower primary age groups, not confined to the limited coverage of life skills as at present.